Liquid-liquid extraction intensification by micro-droplet rotation in a hydrocyclone - Yuan Huang (Nature Portfolio, 2017)
Abstract The previous literature reports that using a hydrocyclone as an extractor intensifies the mass transfer and largely reduces the consumption of extractant from 1800–2000 kg h−1 to 30–90 kg h−1. However, the intensification mechanism has not been clear. This paper presents experimental and numerical methods to study the multi-scale motion of particles in hydrocyclones. In addition to the usually considered translational behavior, the high-speed rotation of dispersed micro-spheres caused by the anisotropic swirling shear flow is determined. The rotation speeds of the tested micro-spheres are above 1000 rad s−1, which are much larger than the instantaneous rotation speed in isotropic turbulence. Due to the conical structure of a hydrocyclone, the rotation speed maintains stability along the axial direction. Numerical results show that the particle Reynolds number of micro-droplets in a hydrocyclone is equal to that in conventional extractors, but the particles have high rotation speeds of up to 10,000 rad s−1 and long mixing lengths of more than 1000 mm. Both the rotation of micro-droplets along the spiral trajectories and the intense eddy diffusion in a hydrocyclone contribute to the extraction intensification.